ANALISIS PERMASALAHAN DALAM PENGGUNAAN PLATFORM SEBAGAI MEDIA PEMBELAJARAN BIOLOGI: STUDI KASUS PADA SMA NEGERI 1 TARAKAN - Rani Rizqi Afiah; Fadhlan Muchlas Abrori; Fitri Wijarini (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2022)
Abstract: This study aims to analyze the problems in using the platform as a medium for learning biology for class X students at SMA Negeri 1 Tarakan. The research method uses a qualitative approach with an explanatory case study type of research. The research subjects were 59 students of SMA Negeri 1 Tarakan class X MIPA. The data was obtained from the results of online interviews using the zoom meeting platform. The results obtained in the communication aspect 39 students said they had problems, in the media aspect in the form of design 18 students said they had problems, in the media aspect in the form of effectiveness 19 students said they had problems, in the content aspect 18 students had problems and on the technical aspect. internet 59 students said they had problems. Based on the results of research and data analysis, it can be seen that in every aspect there are problems in using the platform as a medium for learning biology in class X MIPA SMA Negeri 1 Tarakan. Keywords: Analysis, Platform, Aspect